Evaluasi Jaringan dan Interaksi Tim Sukses Pileg Tahun 2019 Melalui Social Network Analysis (SNA) - Nining Fitriani; Irwan Sembiring; Kristoko Dwi Hartomo (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2020)
The 2019 elections in Indonesia was slightly different from the previous elections because the elections were held simultaneously. It made more difficult for the community to make their choices. Public was faced with a larger number of candidates who were not necessary known as legislative candidates’ socialization is very important. This research discussed the process of network formation and network structure that was formed. Data collection was carried out through observation, interviews and questionnaires with 50 respondents as research samples. The data obtained were processed using the UCINET tool which was then analyzed using Social Network Analysis (SNA). The results showed that the process of network formation occurred because of interpersonal contact between actors, the experiences of being a successful team and relationships history between actors. The network structure formed was closed with a high level of communication density that is 0,976. It was meant that all actors made communication each other intensively. The actor who became the network booster was actor id#02 which always appears in every click that was formed.